Tropical forest remnants as shelters of avian diversity within a tourism development matrix in Yucatan Peninsula, Mexico - Ramírez-Albores, Jorge E. (2018)
Tropical forests have undergone extensive transformation because of increasing tourism development, in addition to historic clearing for agricultural and cattle grazing activities. Altogether, these activities have had an important effect on bird diversity, reducing the habitat available to many species. In this study, the role of tropical forest remnants located between different land use types was evaluated for species diversity, composition, and distribution of the bird community at Akumal region in Quintana Roo, Mexico. Point counts were used to quantify the avifauna by habitat, and Shannon´s and Simpson´s diversity index were used to determine bird diversity. Additionally, bird species were classified according to seasonality and trophic guild by type of habitat. A total of 160 species and 50 families was recorded, of which 100 species were permanent residents, 47 winter visitors and 11 transients. Mature tropical forest and tropical forest remnants had higher species richness than those of modified environments. This study supports the importance of tropical forest remnants as shelters for bird species in landscapes with tourism developments, and the relevance of these remnants to maintaining high bird diversity. Rev. Biol. Trop. 66(2): 799-813. Epub 2018 June 01.